CHARACTERIZATION OF SUB-MICROMETER FUME PARTICLES IN MMA WELDING OF SHIPBUILDING STEEL WITH DIFFERENT TYPES OF ELECTRODES - Celebi, Ugur Bugra; Mert, Tolga; Bilgili, Levent; Senoz, Kutsi Mert; Ekinci, Serkan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Arc welding process is a significant source of by-products such as metal particulates and noxious gases. It is vital to characterize aerosols and define particle composition and size in order to make an assessment for a welder's exposure to welding fume since welding has been associated not only with many respiratory problems such as cough, chronic bronchitis, and asthma but also lung cancer. In this study, manual metal arc (MMA) welding of shipbuilding steel were realized with rutile, basic and cellulosic covered electrodes using variety of parameters. The most and the least fume generating covered electrodes and parameter combinations were analyzed in terms of fume particle composition and morphology. Results were evaluated with regard to occupational health and safety as well as environmental effects.
Keywords: Fume; particle composition; MMA welding; shipbuilding steel; occupational health and safety; SIZE DISTRIBUTION; EXPOSURE; MANGANESE; PULMONARY; Environmental Sciences & Ecology